The Comparison of Parameter Estimation in Exponential Distribution using Maximum Likelihood Method and Bayesian Method - Mada, Grandianus; Salsinha, Cecilia Noviyanti; Mun, Beatrix Farena (Universitas Negeri Padang, 2023)
This study aims to compare the parameter estimation process on the exponential distribution using the maximum likelihood method and the Bayesian method on service data at Bank BRI Atambua Branch. The result of processing data on 100 service time data obtained parameter values for the maximum likelihood method = 0,050942 and the Bayesian = 1,0008. By using the Akaike Information Criterion (AIC) feasibility test for these parameters, the AIC value for the maximum likelihood method was 797,4122 and the AIC value for the Bayesian method was 3.931,1002 so it can be concluded that the maximum likelihood method is better used to estimate parameters than Bayesian method.